THE ANALYSIS OF EDUCATION SERVICE QUALITY AT PANTI SOSIAL BINA REMAJA AND KARYAWAN IT A SOCIAL DEPARTEMENT OF CENTRAL KALIMANTAN PROVINCE - Yesni Nopy; Wiyogo (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2015)
Bina Remaja Social Camp andKarya Wanita of Office of Social Services is one of Central Kalimantan provincial government programs that engages in: Social Welfare Service Center, Center for Information and consultation of social welfare, Social Welfare Development Center. Implementation of the quality program is an important point to the successful implementation of the program. Improved quality is very influential on the results/outcomes such as student proxies as the output. From the results of research using Importance Performance Analysis, it obtained variables that affect the quality of the services contained in quadrant A of Catersian diagram which are : the variable P14 on the availability of information/communication among alumni become important, variable P18 on the availability of a library/reading room or other resource center is adequate to use. The variable P19 on the availability of internet facilities/computer either be chosen by respondents, variable P21 regarding the building/classroom and workshop space in accordance with the designation. At P22 variable attributes sightly, comfortable and helps the learning be chosen by respondents. Next on the variable P25 on the attractive layout space for students and P27 variables regarding health and safety policies are properly supervised, the variable P28 is on the variation ofgood and interesting learning model, then the variable P34 is on the well-explained program to the other party (the owner of the internship place) and P37 on feedback from other users on a regular basis.